Perlindungan Hukum Pendaftaran Jaminan Fidusia Secara Online Melalui Kantor Notaris Nurhasanah, SH, M.Kn - Supeno Supeno; Sylvia Rossanty Rossadi; Fachruddin Razi (Universitas Batanghari Jambi, 2022)
This study aims to identify and identify: (1) the implementation of fiduciary guarantee registration at the law and human rights office through the Notary Nurhasanah, SH, M.Kn office, (2) online obstacles in registering fiduciary guarantees at the law and human rights office through Notary office of Nurhasanah, SH, M.Kn and (3) solutions and solutions in overcoming obstacles in registering fiduciary guarantees at the law and human rights office through the office of Notary Nurhasanah, SH, M.Kn. This research is an empirical research research using a sociological juridical approach, which is a type of research that emphasizes field research based on data obtained from field research or certain places. The resource persons of this research are Notary Nurhasana, SH, M.Kn. The sampling technique used is purposive sampling. The analytical method used in this research is qualitative analytical thinking method and the conclusion is drawn using inductive thinking method. The results of this study indicate that the registration of fiduciary guarantees with this online system makes it easier for notaries to register fiduciary guarantees and does not take a long time where registration can be completed within a few minutes within a period of 30 (thirty) days from the signing of the fiduciary guarantee deed in order to obtain the legal force of the fiduciary guarantee deed. Obstacles in the electronic fiduciary registration process are incomplete data provided by the bank, and the unprepared Information Technology (IT) device to support the implementation of national electronic fiduciary registration. new fiduciary guarantee and immediately register the fiduciary guarantee online through a notary.